Social valuation of coastal wetlands in northwestern Mexico - Mayra Isabel; Ruiz Luna, Arturo (Acta Universitaria, 2023)
Wetlands provide the necessary ecosystem services for human well-being; however, their value and importance have been mainly estimated from an economic perspective, providing relevant information that does not necessarily contribute to their conservation, and sometimes displacing other forms of management defined by the close or direct beneficiaries. Based on this, we estimated the social value that local beneficiaries assign to coastal wetlands and their ecosystem services in southern Sinaloa, from a participatory, spatially explicit methodological framework. Findings suggest that the social value is associated with the location where the beneficiaries live, with the presence of provision services with economic value offered by wetlands, as well as with the social conditions that favor environmental education. Issues related to history and spirituality had little relevance in the evaluation of wetlands.